History of law, Rule of law and republic in Latin America: closer than farther apart - Figueroa Gutarra, Edwin (2024)
The history of law represents a dynamic and not a static concept, to the extent that its full conceptual understanding allows for a better understanding of the legal phenomena of the present. Similarly, the transition of Latin American countries towards republican forms of government invariably leads us to the emancipatory processes of the 19th century. We maintain that the consolidation of the idea of the rule of law was fundamental in this transition and, in this sense, represented, through the dissemination of the ideals of freedom and equality, as well as the codification and constitutionalization of the legal system, the notion of the constitutional state, as the most advanced form of the rule of law.